Multiple Intraosseous Calvarial Hemangiomas Mimicking Metastasis from Renal Cell Carcinoma. (21st October 2007) - Malde, Rohit; Moss, Tim; Malcolm, George; Whittlestone, Tim; Bahl, Amit
Abstract : Renal cell carcinomas are known to metastasise to the bones in the form of lytic lesions. However, not all osteolytic lesions in patients with renal cell carcinoma are metastatic in nature. The report describes the case of a 68-year old lady who was diagnosed with a renal cell carcinoma 3 and half years back and treated with radical nephrectomy along with excision of an inferior vena cava tumour thrombus. The tumour was completely excised and she remained disease free till date. Subsequently, multiple lytic lesions were detected incidentally on the cranial vault, which on biopsy demonstrated intraosseous hemangioma. Though it is well known that renal cell carcinomas can metastasise to the bones in the form lytic lesions, it is important for clinicians to remember a few other differentials, one of which would be an intraosseous hemangioma, which is a benign pathology. Many times patients would be treated as having metastatic disease merely on radiological findings. In this case report, there was a high index of radiological suspicion for metastases, however establishing diagnosis by biopsy prevented overtreatment in this instance.